Mapping cumulative impacts of mining on sediment retention ecosystem service in an Australian mining region. Issue 1 (2nd January 2018) - Wang, Zhenyu; Lechner, Alex Mark; Baumgartl, Thomas
ABSTRACT: Mining development can potentially lead to cumulative impacts on ecosystems and their services across a range of scales. Site-specific environmental impact assessments are commonly assessed for mining projects; however, large-scale cumulative impacts of multiple mines that aggregate and interact in resources regions have had little attention in the literature and there are few examples where regional-scale mining impacts have been assessed on ecosystem services. The objective of this study is to quantify regional-scale cumulative impacts of mining on sediment retention ecosystem services. We apply the sediment delivery ratio model of Integrated Valuation of Ecosystem Services and Trade-offs to calculate and map the sediment retention and export using a synthetic catchment model and a real case study under different mining scenarios in an Australian mining region. Two impact indices were created to quantify the cumulative impacts associated with a single mine and the interactions between multiple mines. The indices clarified the magnitude of impacts and the positive/negative impacts associated with regional-scale sediment retention and export. We found cumulative impacts associated with multiple mines' interaction occurred but the influence of these interactions was relatively weak. This research demonstrated the potential for utilising ecosystem services modelling for the quantitative assessment of the cumulative impacts. Such research provide decision-makers and planners with a tool for sustainable regional and landscape planning that balances the needs of mining and the provision of ecosystem services.